SMA actuated prosthetic finger design [SHA Eyleyicili Protez Parmak Tasarimi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
The proposed work will cover a mechanical design that imitates natural shape and posture of anatomic finger and design of Shape Memory Alloy (SMA) actuators that mimics natural functions of a finger. The best mechanical finger design lies in imitating the complex structure (anatomy) of the human finger with all its bones, joints, muscles, tendons and their connections as close as possible. At this point shape memory alloys are good potential with its muscle like working principles, SMA actuators are placed on phalanges to provide finger movements. © 2016 IEEE.
Keywords: actuators; prosthetics; Shape memory alloy